STUNTING PREVENTION BY STRENGTHENING POSYANDU AND FAMILY APPROACH THROUGH HEALTH LITERACY IN MAJENE REGENCY, WEST SULAWESI PROVINCE - Evawaty1, Nurhaedar Jafar2*, Healthy Hidayanty2, Sudirman Natsir3, Razak Thaha2, Ridwan Amiruddin4, Citrakesumasari2, Lucy Widiasari2, Rusli Taher5, Abdul Thalib6 (Chelonian Research Foundation, 2023)
Background: The second highest case of stunting in Indonesia is West Sulawesi Province. Stunting causes stunted child growth and development which ultimately has an impact on the quality of human resources. Stunting prevention begins through strengthening posyandu and family approaches. Objective: The purpose of this study is to prevent stunting by strengthening posyandu and family approach through health literacy in Majene District, West Sulawesi Province. Method: The research method used is qualitative research with phenomenological design. The informants in this study were 103 Baduta mothers who were exclusively breastfed, and lived in rural areas of Pamboang District and Tameroddo District. The data was analyzed using content analysis through the N-Vivo 12 application. Results: The results showed that stunting prevention in Majene district, West Sulawesi province can be seen through the variables of Health Care Support, Family Support, Access to Information, and Expected Education. The most felt support for health workers is by health workers coming to people's homes to make direct visits, the biggest Family Empowerman is care assisted by Grandma, access to the most information obtained at Posyandu, The most expected education is group / personal education accompanied by practice and the availability of pocket books (Booklets). Conclusions and Suggestions: Stunting prevention can be done in Majene District, South Sulawesi Province by strengthening posyandu and family approaches through group health education accompanied by practices and booklets as a form of health literacy. So it is recommended to the government and relevant stakeholders to focus on strengthening Posyandu and families as the spearhead of the stunting prevention movement in Majene District. Keywords: Stunting Prevention, Posyandu, Family Approach, Health Literacy